I saw it in Spore - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In recent letters to Mailbox, readers have reported these uses of Spore farmers adapting anti-erosion technologies teaching material in schools and universities staff training in service agencies reproduction in newsletters, annual reports ...